(untitled) (European Journal of Pure and Applied Mathematics, 2023)
Schultz polynomial is one of the must significant formulas that represent a relationship between the degree’s of vertices in a simple connected graph G and the distances between these vertices. In this work, Schultz and modified Schultz polynomials, as well as their topological indices of chain and ring hexagonal graphs, have been successfully identified.